Food assessment: a discursive analysis of diet talk in interviews with older men who are obese. Issue 8 (2nd August 2020) - Seymour-Smith, Sarah; Gough, Brendan; Matthews, Christopher R.; Rutherford, Zoe
Abstract: Objective: Obesity rates are increasing faster in men than in women, with particular concerns raised regarding older men. However, men are less likely than women to engage in weight-loss activities such as dieting, typically constructed as a feminine practice. Previous research has argued that men's food consumption is notably different and unhealthier than women's. The novel contribution of this article is an analysis of food assessments in order to explore how older men (mostly) undergoing weight management programmes make sense of changes in their nutritional intake. Design: Semi-structured interviews were conducted with 30 men who were obese, 27 of whom were engaged in weight loss programmes. Discursive psychology was employed to analyse the data. Results: In contrast to other research, participants constructed nutritional advice as enlightening. Participants worked up 'ownership' and pleasure assessments to certain food choices which they contrasted with new, less calorific, eating practices. Moreover, new diets were constructed as acceptable. Conclusion: Our study contributes new insights about how nutritional advice impacts upon preconceived (mis)understandings of healthy eating practices. During the interviews, men positioned themselves as educators – health promoters might usefully develop nutritional advice in collaboration with men who have successfully changed their diets for optimum effect.